2020
DOI: 10.1093/poq/nfaa040
|View full text |Cite
|
Sign up to set email alerts
|

Using Cognitive Mapping to Study the Relationship between News Exposure and Cognitive Complexity

Abstract: Cognitive complexity is a concept that allows scholars to distinguish unidimensional thinking from multidimensional thinking, which allows citizens to identify and integrate various perspectives of a topic. Especially in times of fake news, fact-free politics, and affective polarization, the news media would ideally foster such complex political understanding. The current paper introduces the method of cognitive mapping to measure cognitive complexity regarding citizens’ understanding of the financial crisis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…The future is uncertain and grasping it requires cognitive complexity – that is, the ability to consider the many different sides of a matter and to create linkages between different things (e.g. Boukes et al, 2021; Van Hiel and Mervielde, 2003). Education is positively associated with cognitively complex thinking (Milburn and McGrail, 1992), suggesting that it could also predict future-oriented thinking.…”
Section: Future Orientation and Voter Behaviourmentioning
confidence: 99%
“…The future is uncertain and grasping it requires cognitive complexity – that is, the ability to consider the many different sides of a matter and to create linkages between different things (e.g. Boukes et al, 2021; Van Hiel and Mervielde, 2003). Education is positively associated with cognitively complex thinking (Milburn and McGrail, 1992), suggesting that it could also predict future-oriented thinking.…”
Section: Future Orientation and Voter Behaviourmentioning
confidence: 99%
“…Based on findings of political news and its influence on political knowledge (e.g., [45][46][47][48][49]), scholars agree that the news media (e.g., television, newspaper, radio, the Internet) play a crucial role in mediating financial information to the public (e.g., [21,50]). Interestingly, the argument that individuals might use the news media to get an idea of the current economic situation or economic forecasts was put forward already, around thirty years ago [51].…”
Section: Economic News Use and Financial Understandingmentioning
confidence: 99%
“…However, the picture is varied and can depend on external events and the national context. A recent study using cognitive mapping has shown that while general news consumption is connected to a lower complex understanding of the Global Financial Crisis 2007-2009 (GFC) among Dutch citizens, news uses specifically dealing with the GFC are related to higher cognitive complexity when making sense about the GFC but only among the less-educated citizens [46]. Conversely, another study conducted in the Netherlands implies that more news consumption is not necessarily correlated with a better understanding of economic indicators, such as inflation [56].…”
Section: Economic News Use and Financial Understandingmentioning
confidence: 99%
“…The method was developed and introduced by the philosopher Paul Thagard (2010) and used primarily in conflict research as a tool to depict and communicate divergent perspectives. In this regard, CAMs might be considered an extension of cognitive maps (e.g., Boukes et al, 2020) that allow the integration as well as the differentiation of cognitive concepts (Conway et al, 2014; Neumann, 1981; Suedfeld, 2010; Tetlock, 1983). While these cognitive maps are able to depict the “cognitive complexity” of a given topic, CAMs additionally allow one to depict the affective valences—that is, whether a concept is considered as positive, negative, neutral, or ambivalent.…”
mentioning
confidence: 99%